Analysis of mortality in patients with leptospirosis according to materials of Zaporizhzhia regional infectious diseases hospital - Mohammad, Osman El-youssef (Запорізький державний медико-фармацевтичний університет, 2025)
The purpose of the study: analysis of deaths in patients with Leptospirosis based on materials of ZRIDH.
Keywords: тези доповідей